Quantum-Mechanical Brayton Engine for the Nonrelativistic Particle Trapped in a Symmetric Potential Box - Fikri Abdillah; Yohanes Dwi Saputra (POSITRON, 2020)
A theoretical quantum Brayton engine research has been carried out using a potential box system to increase its thermal efficiency. The method applied in this research is a classical thermodynamics system model in the form of a piston tube containing a monatomic ideal gas analogous to a quantum model in the form of a potential box containing one particle.  The efficiency formulation of the quantum Brayton engine obtained from this study is following the classical version. However, the efficiency value obtained on a quantum Brayton engine is higher when compared to its classic. It happens because the value of the Laplace constant owned by the Brayton quantum version is 3, while the classic version is 5/3.